Strategi Pemasaran yang Efektif: Meningkatkan Omzet Penjualan Roti dalam Tinjauan Hukum Ekonomi Islam di Mawaddah Bakery Bandar Lor Kediri - Juni Iswanto; Subekan Subekan; Dewi Fitrtotus Sa`Diyah; Mastur Mastur; Agus Tohawi (Journal on Education, 2023)
This study delves into the marketing strategies of Mawaddah Bakery, located in Bandar Lor, Kediri, with the aim of increasing sales revenue and examining the perspectives of Islamic economic law. Utilizing a descriptive and qualitative case study approach, primary data sources include the business owner, supplemented by secondary data in the form of documentation. Research findings indicate that Mawaddah Bakery has successfully implemented an effective marketing mix strategy (4Ps). Strategies related to product, price, place, and promotion are executed well, encompassing product quality, pricing, strategic location, and consumer service promotion. In the context of Islamic economics, these strategies align with Sharia principles, emphasizing characteristics such as devotion, realism, humanism, and ethics. The strategies adhere to the characteristics of Sharia marketing and the Islamic marketing strategy system. This reflects compliance with Islamic economic values in a business context.